Diabetes Secondary to Acromegaly: Physiopathology, Clinical Features and Effects of Treatment - Ferraù, Francesco; Albani, Adriana; Ciresi, Alessandro; Giordano, Carla; Cannavò, Salvatore (Frontiers in Endocrinology, 2018)
Acromegaly is a rare disease due to chronic GH excess and to the consequent increase in IGF-1 levels. Both GH and IGF-1 play a role in intermediate metabolism affecting glucose homeostasis. Indeed, chronic GH excess impairs insulin sensitivity, increases gluconeogenesis, reduces the glucose uptake in adipose tissue and muscle and alters pancreatic β cells function. As a consequence, glucose metabolism alterations are a very frequent complication in acromegaly patients, further contributing to the increased cardiovascular risk and mortality. Treatment modalities of acromegaly differently impact on glucose tolerance. Successful surgical treatment of acromegaly ameliorates glucose metabolism abnormalities. Drugs used to treat acromegaly patients may per se affect glucose homeostasis, therefore influencing patients’ management. Indeed pegvisomant has been shown to positively impact on glucose metabolism, while somatostatin analogues, especially pasireotide, can cause hyperglycaemia. On the other hand, robust data on the effect of dopamine agonists on glycaemic profile are still lacking. This review summarizes the available data on diabetes mellitus in acromegaly patients, with a focus on the potential effects of the medical treatment of the disease on glucose homeostasis, providing an overview of the current state of the art.